Model-based insulin-nutrition administration for glycemic control in Malaysian critical care: First pilot trial - Abu-Samah, Asma; Ahamad, Nurhamim H.; Abdul Razak, Normy Norfiza; Suhaimi, Fatanah M.; Jamaludin, Ummu Kulthum; Md Ralib, Azrina; Mat Nor, Mohd Basri; Pretty, Christopher G.; Dickson, Jennifer L.; Chase, Geoffrey G. (Springer Verlag, 2018)
Stress-induced hyperglycemia is prevalent in critical care, even in patients with no history of diabetes. Control of blood glucose level with tight insulin therapy has been shown to reduce incidences of hyperglycemia leading to reduced mortality and improved clinical outcomes. STAR is a tablet-based glucose control protocol with a specialized user interface into which insulin and nutrition information can be entered and predicted. This research describes the first clinical pilot trial of STAR approach in International Islamic University Hospital, Kuantan, Malaysia. The clinically specified target for blood glucose level is between 4.4 and 8.0 mmol/L. Seven episodes (of 359 h) were recruited based on the need for glucose control. Overall, 43.93% of measurement are in the range of 4.4–8.0 mmol/L band. The blood glucose median is 8.30 [6.32–10.00] mmol/L with only 1 patient having below than 2.22 mmol/L which is the guaranteed minimum risk level. This pilot study shows that STAR protocol is a patient specific approach that provides a good glycemic control in critically ill patients. Nevertheless, its implementation in Malaysian intensive care environments requires modifications and improvements in certain areas.